Limites para o uso de empresa-veículo no planejamento tributário - Peres, Rogério Garcia (2019)
This study aims to critically analyze the criteria used by the Brazilian administrative tax courts, namely, the Conselho Administrativo de Recursos Fiscais – CARF, to evaluate the legality of conduit companies as a means of stemming and deterring tax burden in tax planning. Initially, propaedeutic questions with regard to the Law Theory as a social system in which language has a referential function will be addressed. Furthermore, a concept of tax planning, addressing the notions of tax mitigation, tax avoidance and tax evasion, as well as the evolution of the legal norms regulating the powers of the tax authorities in tackling tax planning structures will be supported. In addition, the author analyzes some institutes created by case-law often used to disqualify structures or transactions carried out within the scope of tax planning. Additionally, some relevant comments will be made concerning the essential elements of a company in Private Law, especially in Commercial Law, in order to assess the criteria that determine the validity and lawfulness of the company as a legal entity. Finally, the validity of the arguments and criteria used by CARF in the judgment of tax planning using shell corporations as a means of curbing or deterring taxation will also be challenged